(untitled) (Journal of Society of Surgeons of Nepal, 2019)
Social media has become an integral part of modern life-style. It is ubiquitously available in computer, smart televisions, and hand held devices like tablets, ipads and mobile phones. As per www.statista.com, there are about 2.27 billion monthly active facebook users as of January 2019.